Chapter Il diritto del lavoro e i valori nella crisi - Fontana, Giorgio (Studi e saggi, 2022)
The essay deals with the relationship between values and labor law following in the first part a logical thread that moves from two essential foundations: Europe and the trade union. The author considers the crisis of these references as a crucial moment in the transformation of the value system. The dialectic between the different perspectives of labor law and the antithesis on the same vision of work in post-modern society are now reflected in the changes in the world of work. The current situation is being crossed by the pandemic crisis, which is also changing the way of understanding work. The prospect of degrowth and the crisis of the capitalist development model impose problems and new values, a renewed relationship between ethics and labor law.